Recuperating Lung Decoction Attenuates the Oxidative Stress State of Chronic Obstructive Pulmonary Disease by Inhibiting the MAPK/AP-1 Signal Pathway and Regulating γ-GCS - Li, Chunlei (Evid Based Complement Alternat Med, 2017)
Purpose/Objective. To evaluate the effects of Recuperating Lung Decoction (RLD) on the indices of oxidative stress in a rat model of COPD and detect the indices of the MAPK/AP-1/γ-GCS signal pathway for a further survey of the possible targeting site of RLD. Methods/Materials. The rats of COPD were treated with RLD. The protein levels of glutathione (GSH), oxidized glutathione (GSSG), 8-hydroxy-2-deoxyguanosine (8-OHdG), and 4-hydroxynonenal (4-HNE) were measured. In addition, the levels of key signaling molecules (extracellular signal-regulated kinases [ERK], the c-jun N-terminal kinase [JNKs signal pathway], and p38 MAP kinase [p38MAPK], AP-1 proteins [C-fos, C-jun], and γ-glutamyl-cysteine synthetase [γ-GCS-h]) of the MAPK/AP-1/γ-GCS-h signal pathway were assessed. Results. After treatment, the protein level of GSH and the ratio of GSH/GSSG were increased and the amounts of 8-OHdG and 4-HNE were decreased significantly in lung tissues when compared with the nontreated COPD group. Further results showed that the RLD could effectively inhibit the MAPK pathway by inactivation of p38MAPK and ERK and could also downregulate the AP-1 and the γ-GCS-h genes expressions in both protein and mRNA levels. Conclusion. RLD might improve the state of oxidative stress by downregulation of the expression of γ-GCS-h gene by inhibition of the MAPK/AP-1 pathway, thereafter enhancing the ability of antioxidation in COPD.